Strategi Peningkatan Kesadaran Masyarakat Dalam Mengelola Sampah Di Desa Pematang Johar Kecamatan Labuhan Deli - Lubis, Devi Rafidayani; Madya, Efi Brata (Jayapangus Press, 2024)
One of the main problems in Indonesia is waste. Piles of waste are an inseparable part of life because waste will continue to exist along with human activities. This research aims to explain the strategies implemented by the village government to increase community awareness in managing waste and the obstacles faced in implementing the strategy in Pematang Johar village, Labuhan Deli sub-district. This study uses a qualitative method with a descriptive approach. The place of this study was Pematang Johar Village, Labuhan Deli Sub-district. Data collection techniques were observation, interview and documentation. The data analysis technique was carried out by data reduction, data display, and conclusion drawing. Based on the results of the study, it shows that one of the effective strategies to increase public awareness in managing waste is through the establishment of waste banks. The existence of waste banks can encourage community participation in the waste management process, starting from collection, sorting, to the transformation of waste into materials that can be reprocessed with economic value. In addition, there are several obstacles faced in the implementation of waste banks in Pematang Johar Village such as time constraints due to daily work and financial constraints in running the operations of the suka mulia waste bank, including operational costs, equipment acquisition, and employee payroll. The conclusion of this research is that one way to increase the awareness of Pematang Johar Village residents about waste management is to implement a waste bank program. The existence of a waste bank in this village can encourage active community involvement in activities. However, there are several obstacles in the implementation of this program in Pematang Johar Village, such as financial constraints. In addition, many residents have difficulty managing their time to participate in waste bank activities.